2018
DOI: 10.1590/1678-5150-pvb-5786
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Staphylococcus aureus virulence genes in milk of cows and goats with mastitis

Abstract: The present study determined the frequency of Staphylococcus aureus virulence genes in 2,253 milk samples of cows (n=1000) and goats (n=1253) raised in three different geographical regions of the state Pernambuco, Brazil. The presence of genes of virulence factors associated to adhesion to host cells (fnbA, fnbB, clfA and clfB), toxinosis (sea, seb, sec, sed, seg, seh, sei, tsst, hla and hlb), and capsular polysaccharide (cap5 and cap8) was evaluated by PCR. A total of 123 and 27 S. aureus strains were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
2
8
0
2
Order By: Relevance
“…Our results corroborate with Marques et al (2017) that showed a high abundance of genes icaA and icaD in S. aureus isolates, producing biofilm in samples from bovine intramammary infections in Brazil. Acosta et al (2018) reported a high frequency of fnbA (94%), fnbB (81.3%), hlA (88%) and hlB (88.3%) genes in S. aureus from milk samples, and these genes were more abundant in samples from bovine milk than goat milk in a recent study developed in cow and goat herds raised in three different geographical regions of the state of Pernambuco, Brazil, and these results corroborate with our data.…”
Section: Analyses Of Vfs Detection Of S Aureussupporting
confidence: 91%
“…Our results corroborate with Marques et al (2017) that showed a high abundance of genes icaA and icaD in S. aureus isolates, producing biofilm in samples from bovine intramammary infections in Brazil. Acosta et al (2018) reported a high frequency of fnbA (94%), fnbB (81.3%), hlA (88%) and hlB (88.3%) genes in S. aureus from milk samples, and these genes were more abundant in samples from bovine milk than goat milk in a recent study developed in cow and goat herds raised in three different geographical regions of the state of Pernambuco, Brazil, and these results corroborate with our data.…”
Section: Analyses Of Vfs Detection Of S Aureussupporting
confidence: 91%
“…The pathogenicity of S. aureus is related to its ability to produce and secrete a variety of virulence factors that play a role in the colonization, invasion, and degradation of host cells, immune evasion, and bacterial spread (Pietrocola et al 2017;Cheung et al 2021). The fnbA and clfA genes are virulence factors implicated in host cell adhesion, while the sea, tst, and hla were reported to be associated with toxins (Acosta et al 2018). The present study revealed that virulence factors fnbA, hla, clfA, and tst genes were detected in S. aureus isolates derived from animal and human samples.…”
Section: Virulence Marker Genesmentioning
confidence: 51%
“…None of the S. aureus isolates obtained in the present study harbored the sea gene. The existence of fnbA, clfA, hla, sea, and tst in isolates from animal samples has been previously reported by Acosta et al (2018). Another study reported the presence of the tst gene, but not the sea gene in the isolates from animal (raw milk) and human samples (Vitale et al 2019).…”
Section: Virulence Marker Genesmentioning
confidence: 52%
“…Sample selection criteria. Milk samples were collected from 1000 cows from 24 bovine herds from the state of Pernambuco, Brazil as described by (Acosta et al 2018). Only milk samples from cows with clinical signs of mastitis and that had not been treated with antibiotics for at least three weeks were used in the present study.…”
Section: Methodsmentioning
confidence: 99%